1994
DOI: 10.1577/1548-8659(1994)123<0217:ugkftn>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucuronyltransferase Kinetics for 3-Trifluoromethyl-4-nitrophenol (TFM) in Fish

Abstract: Studies were conducted to address glucuronidation of 3‐trifluoromethyl‐4‐nitrophenol (TFM) in sea lampreys Petromyzon marinus, channel catfish Ictalurus punctatus, rainbow trout Oncorhynchus mykiss, and bluegills Lepomis macrochirus. The ability of these species to biotransform TFM was investigated by determining the kinetics of UDP‐glucuronyltransferase (UDPGT; also known as glucuronosyltransferase) in vitro from hepatic microsomal preparations. Maximal velocity (Vmax, nmol/min·mg) for UDPGT activity toward T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…TFM has similar effects on oxidative ATP production in rainbow trout mitochondria (Birceanu et al 2011), suggesting that any TFM-induced perturbations such as reduced internal ATP, PCr, and glycogen concentrations and lactacidosis, would be quickly reversed in nontarget fishes as well. Given that most fishes have greater capacity to clear TFM from their bodies (Dawson et al 2002;Vue et al 2002) than do sea lampreys (Kane et al 1994), it is likely that any physiological impairment arising from incidental exposure to TFM would be minimal, but this possibility needs to be confirmed by additional laboratory and field-based studies.…”
Section: Conclusion and Implications For Sea Lamprey Controlmentioning
confidence: 99%
“…TFM has similar effects on oxidative ATP production in rainbow trout mitochondria (Birceanu et al 2011), suggesting that any TFM-induced perturbations such as reduced internal ATP, PCr, and glycogen concentrations and lactacidosis, would be quickly reversed in nontarget fishes as well. Given that most fishes have greater capacity to clear TFM from their bodies (Dawson et al 2002;Vue et al 2002) than do sea lampreys (Kane et al 1994), it is likely that any physiological impairment arising from incidental exposure to TFM would be minimal, but this possibility needs to be confirmed by additional laboratory and field-based studies.…”
Section: Conclusion and Implications For Sea Lamprey Controlmentioning
confidence: 99%
“…Cortisol has been shown to induce liver glycogenolysis in fish [ 37 ], and, therefore, the elevation of cortisol levels post-TFM exposure may be required to facilitate the supply of G6P substrate for glucuronic acid production and TFM elimination in the hours immediately following exposure. Most non-target fishes, rainbow trout in particular, do have a high capacity to detoxify TFM [ 11 , 16 ] and would rely on glucuronidation to eliminate the lampricide from the body [ 12 , 43 ]. Moreover, TFM and TFM-glucuronide have been detected in the muscle fillet of fish up to 12 h following a routine TFM application [ 16 ], suggesting that detoxification still occurs for several hours following exposure to the lampricide.…”
Section: Discussionmentioning
confidence: 99%
“…are conjugated with glucuronic acid via UDPGTs (George, 1994). Among the drugs and pesticides that are conjugated via UDPGTs are chloramphenicol (Cravedi et al, 1985), organophosphates (Takimoto et al, 1987), and phenols (Lech, 1973;Kane et al, 1994). Aflatoxicol B1 glucuronide is also formed in rainbow trout exposed to this hepatocarcinogen (Loveland et al, 1984).…”
Section: Udp-glucuronosyltransferase (Udpgt) Kineticsmentioning
confidence: 99%
“…In the past, differences in UDPGT-based conjugation have helped to understand distinct sensitivities among fish species to pollutants or drugs. Kane et al (1994) found that the lower V max /K m ratio in sea lamprey (Petromyzon marinus) as compared to channel catfish, rainbow trout and bluegill helped to explain a high sensitivity to 3-trifluoromethyl-4-nitrophenol (TFM), due to lower UDPGT-based conjugation.…”
Section: Udp-glucuronosyltransferase (Udpgt) Kineticsmentioning
confidence: 99%